REPRESENTATION OF JAPANESE CULTURE IN THE FILM NIHONJIN NO SHIRANAI NIHONGO (A SEMIOTIC STUDY) - MILENIA SEVTIANI; Izmayanti, Dewi Kania; Irma; Amril, Oslan (Hikari: Jurnal Bahasa dan Kebudayaan, 2024)
Abstract Japan has succeeded in maintaining its culture from traditional to modern culture. Thanks to its success, Japan has been highly regarded by other countries. The large number of enthusiasts outside Japan who watch anime films proves that Japanese culture is not only popular in Japan but also outside Japan. One example is the film "Nihonjin No Shiranai Nihonggo," which depicts the love of people outside Japan for Japanese culture. Zen, which represents the art of tranquility, is widely present in Japanese culture. This is the basis for this research, which aims to describe Japanese culture depicted in the film "Nihonjin No Shiranai Nihonggo." The researcher uses Roland Barthes' theory to describe Japanese culture in this film. According to the theory presented by Roland Barthes, meaning is divided into three types: denotation, connotation, and myth. To dissect these meanings, the author uses the literature review method with the note-taking technique. From the 12 episodes, 8 Japanese cultures were found: Furoshiki in episode 2, Hanafuda and Kendou in episode 3, Shouryuuma and kanji in episode 5, Natto in episode 7, the tea-drinking etiquette in episode 8, and omikuji fortune-telling in episode 10. Therefore, we can conclude that Japanese culture can be seen through films and interpreted in terms of connotation, denotation, and myth. Keywords: Nihonjin No Shiranai Nihonggo, Film, Denotative Meaning, Connotative Meaning, Mythical Meaning. Abstrak Jepang sukses menjadi negara yang mempertahankan kebudayaannya dari budaya tradisonal hingga budaya modern. Berkat keberhasilannya tersebut Jepang menjadi sangat disorot oleh negara lain. Banyaknya peminat masyarakat diluar Jepang yang menonton film anime membuktikan bahwa budaya Jepang tidak hanya populer di Jepang namun juga diluar Jepang. Salah satunya adalah Film Nihonjin No Shiranai Nihonggo yang menggambarkan kecintaan masyarakat diluar jepang terhadap budaya Jepang. Zen yang menggambarkan ilmu sebuah ketenangan banyak terkandung di dalam unsur budaya Jepang. Hal inilah yang mendasari penelitian ini dilakukan yaitu untuk mendiskripsikan budaya Jepang yang tergambar dalam film Nihonjin No Shiranai Nihonggo. Peneliti menggunakan teori Roland Barthes untuk menggambarkan budaya jepang yang terkandung di dalam film ini. Menurut teori yang disampaikan oleh Roland Barthes dikatakan bahwa makna terbagi menjadi 3 jenis yaitu makna denotasi, makna konotasi dan juga mitos. Untuk membedah makna tersebut penulis menggunakan metode kajian pustaka dengan teknik simak catat. Dari 12 episode ditemukan 8 budaya jepang yaitu Furoshiki di episode 2, Hanafuda dan Kendou di episode 3, Shouryuuumma dan kanji di episode 5,Natto di episode 7, tata cara minum the episode 8, ramalan omikuji di episode 10. Maka dapat kita simpulkan bahwa budaya Jepang dapat kita bisa melihatnya melalui film dan bisa memaknainya secara konotasi, denotasi, dan juga mitos. Kata Kunci : Nihonjin No Shiranai Nihonggo, Film, Makna Denotasi, Makna Konotasi, Makna Mitos.